Towards a political economy of land: reciprocal rights and duties in private property - Ferreiro, M. F. (2017)
The paper explores some fundamental aspects of a Political Economy of Land such as the definition of rights and duties in legal and ethical terms. The increasing demands of sustainability introduces the need of a critical analysis of this institution with the purpose to explain and improve the present discussion that pursue alternative forms of appropriation and use of natural resources such as land. The responsibility involved in property rights and, thus, its conception in reciprocal terms, is present in some of the most important works of economic thought, namely Classical Political Economy and Old Institutionalism. These theories present important insights to the conception of land and its exploitation. The analysis of the legal rules that define property rights in the Portuguese case stresses the rights and duties involved in property. Besides Law, a Political Economy of Land should consider Ethics, namely Land Ethics. Therefore, the paper presents an essay for the analysis of property rights trough economic, legal and ethical concerns envisaging the design of a Political Economy of Land.